Морфологічні особливості лускового покриву риб роду Barbus (Osteichthyes, Cypriniformes) з України і деяких суміжних територій та їхня роль у систематиці - Романь, А.М. (Вестник зоологии, 2011)
Установлено, что наличие и особенности строения эпителиальных образований на поверхности головы и чешуях рыб, а также форма и структура чешуйной пластинки представителей рода Barbus видоспецифичны. На основании структуры чешуйной пластинки в пределах рода Barbus выделены три группы видов: 1 B. barbus, В. tauricus, B. kubanicus, B. escherichii и B. lacerta; 2 В. waleckii, В. petenyi и B. cyclolepis; 3 B. (Luciobarbus) mursa. Распределение видов по этим группам отвечает современной систематике рода. The presence and features of epithelium structures on surface of head and on scales, shape and structure of the scale plates in fish of the genus Barbus are shown to be species-specific. Based on scale structure the genus Barbus is proposed to be divided into three species groups: 1 – B. barbus, B. tauricus, B. kubanicus, B. escherichii and B. lacerta; 2 – B. waleckii, B. petenyi and B. cyclolepis; 3 – B. (Luciobarbus) mursa. Species distribution according to this groups are fulfils his current taxonomy.